Lonafarnib Inhibits Farnesyltransferase via Suppressing ERK Signaling Pathway to Prevent Osteoclastogenesis in Titanium Particle-Induced Osteolysis - Linke Huang; Linke Huang; Linke Huang; Weiwei Chen; Weiwei Chen; Linhua Wei; Linhua Wei; Linhua Wei; Yuangang Su; Yuangang Su; Jiamin Liang; Jiamin Liang; et al. (Frontiers Media S.A., 2022)
Wear debris after total joint arthroplasty can attract the recruitment of macrophages, which release pro-inflammatory substances, triggering the activation of osteoclasts, thereby leading to periprosthetic osteolysis (PPOL) and aseptic loosening. However, the development of pharmacological strategies targeting osteoclasts to prevent periprosthetic osteolysis has not been fruitful. In this study, we worked toward researching the effects and mechanisms of a farnesyltransferase (FTase) inhibitor Lonafarnib (Lon) on receptor activator of nuclear factor κB (NF-κB) ligand (RANKL)-induced osteoclastogenesis and bone resorption, as well as the impacts of Lon on titanium particle-induced osteolysis. To investigate the impacts of Lon on bone resorption and osteoclastogenesis in vitro, bone marrow macrophages were incubated and stimulated with RANKL and macrophage colony-stimulating factor (M-CSF). The influence of Lon on osteolysis prevention in vivo was examined utilizing a titanium particle-induced mouse calvarial osteolysis model. The osteoclast-relevant genes expression was explored by real-time quantitative PCR. Immunofluorescence was used to detect intracellular localization of nuclear factor of activated T cells 1 (NFATc1). SiRNA silence assay was applied to examine the influence of FTase on osteoclasts activation. Related signaling pathways, including NFATc1 signaling, NF-κB, mitogen-activated protein kinases pathways were identified by western blot assay. Lon was illustrated to suppress bone resorptive function and osteoclastogenesis in vitro, and it also reduced the production of pro-inflammatory substances and prevented titanium particle-induced osteolysis in vivo. Lon decreased the expression of osteoclast-relevant genes and suppressed NFATc1 nuclear translocation and auto-amplification. Mechanistically, Lon dampened FTase, and inhibition of FTase reduced osteoclast formation by suppressing ERK signaling. Lon is a promising treatment option for osteoclast-related osteolysis diseases including periprosthetic osteolysis by targeted inhibition of FTase through suppressing ERK signaling.